2021
DOI: 10.1038/s41433-021-01648-1
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography in Alzheimer’s disease: a systematic review and meta-analysis

Abstract: BACKGROUND:To assess the association between optical coherence tomography angiography (OCTA) retinal measurements and Alzheimer's disease (AD). METHODS: We searched MEDLINE and EMBASE from inception up to October 28th, 2020 for studies assessing the association between OCTA retinal measurements and AD. Estimates from eligible studies were meta-analysed and pooled standardized mean differences (SMDs) between AD patients and healthy participants with corresponding 95% confidence intervals (95% CI) were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…The emerging research on Alzheimer’s disease has benefited from the quantitative OCT/OCTA analyses that have extended into neurodegenerative disorders. Evidence has shown the retinal thickness and microvascular abnormalities associated with Alzheimer’s disease [ 9 ]. Nowadays, OCT/OCTA-based deep learning algorithms have been applied in the classification tasks for various diseases and segmentation tasks, including the delineation of macular edema [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emerging research on Alzheimer’s disease has benefited from the quantitative OCT/OCTA analyses that have extended into neurodegenerative disorders. Evidence has shown the retinal thickness and microvascular abnormalities associated with Alzheimer’s disease [ 9 ]. Nowadays, OCT/OCTA-based deep learning algorithms have been applied in the classification tasks for various diseases and segmentation tasks, including the delineation of macular edema [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rapid development of OCT has sparked great interest in retinal research over the years. Thousands of publications have reported the advanced OCT technology and clinical applications, and systematic reviews and meta-analyses have focused on specific questions of retinal OCT research [ 8 , 9 ]. With the significant growth in the production of research literature, novel approaches are required to review and analyze the trends within the domain of retinal OCT knowledge [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the size of the FAZ appears to get altered during other systemic conditions, including neurodegenerative diseases. Previous studies have shown FAZ widening associated with a decreased vascular density in patients with Alzheimer’s disease [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…AD is characterized by the loss of brain neurons and by cerebrovascular changes in small vessels that are difficult to detect using the available brain imaging technologies [ 8 ]. Due to the similarities between the retinal and cerebral vasculature, which share embryological origin as well as physiological and anatomical properties [ 9 ], it seems logical to use the retina and its vascular network to understand the characteristics of vascular cerebral pathologies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%